Does the Seal Licensing System in Scotland Have a Negative Impact on Seal Welfare? - Nunny, Laetitia; Langford, Fritha; Simmonds, Mark P. (Frontiers in Marine Science, 2016)
This study examined the licensing system that permits seal shooting in Scotland, which was established under Part 6 Conservation of Seals of the Marine (Scotland) Act 2010. Four approaches were used: data were collated and analyzed from both the Scottish Government and Scottish Marine Animal Stranding Scheme; a survey was sent to current license holders and informal interviews were conducted with key stakeholder types. Between February 2011 and the end of October 2015, 1229 gray seals and 275 common seals were reported shot under license to the Scottish Government. The numbers of seals reported as shot has reduced year-on-year since the licensing system was put in place. While some license holders, notably fish farms, were using some non-lethal forms of deterrent to reduce seal-related damage, these were often used alongside seal shooting. Of the seals reported as shot to the Scottish Government, only a small percentage were also reported to the Scottish Marine Animal Stranding Scheme, despite this being a licensing requirement. Only 2.3% of the shot gray seals and 4.5% of the shot common seals were necropsied. There is evidence from these necropsies that some seals had not died instantly or had not been shot in the manner recommended by the Scottish Seal Management Code of Practice. These preliminary results show that more carcasses need to be recovered and necropsied if the welfare implications of current seal shooting practice are to be properly assessed. The current legislation does not specify closed seasons to protect breeding seals and thirty-five per cent of necropsied seals were pregnant gray seals. Seals have also been shot during their lactation periods when pups are dependent on their mothers. This raises significant welfare concerns. The re-introduction of closed seasons specific to each species of seal is recommended along with greater effort to deploy non-lethal methods. Independent assessment of the number of seals being killed would also improve the credibility of the system.